2015
DOI: 10.17265/2161-623x/2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Evaluation of Professional Personality Competencies of Physical Education Teachers Working in High Schools

Abstract: The purpose of the study is to examine the relationship between professional personality competencies of physical education teachers working in high schools and gender, school type, and class variables of students. The study was organised according to the screening model. The study was carried out in a total of 17 schools, 16 state and one private, connected to the Ministry of National Education located in Canakkale province, with 1,254 high school students attending in the academic year [2013][2014]. Of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…While male students rated all subcomponents of professional personality competency as "partly adequate", female students evaluated the "motivational interaction" and "professional enthusiasm and dedication" subcomponents as "completely adequate" and evaluated the other two subcomponents as "partly adequate". These results are comparable with those of Demir and Karagözoğlu (2014) and Demir (2015a). On the other hand, in the study by Safvenbom, Haugen and Bulie (2014), female students were found to be less likely than male students to feel positively towards physical education.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…While male students rated all subcomponents of professional personality competency as "partly adequate", female students evaluated the "motivational interaction" and "professional enthusiasm and dedication" subcomponents as "completely adequate" and evaluated the other two subcomponents as "partly adequate". These results are comparable with those of Demir and Karagözoğlu (2014) and Demir (2015a). On the other hand, in the study by Safvenbom, Haugen and Bulie (2014), female students were found to be less likely than male students to feel positively towards physical education.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, participating secondary school students generally evaluated the professional personality competence of physical education teachers as "partly adequate" or "completely adequate". Studies by Demir (2015a) and Demir and Karagözoğlu (2014) achieved comparable results.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Physical Education activities have been recognized as the most influential aspect that affected the routine physical activities among youths (Sallis & Mc Kenzi, 1991). According to Erdal (2015), PE helps in enhancing students' overall abilities through physical, social, emotional and cognitive activities. Parallel to the aims of the National Educational Philosophy, PE has been incorporated as a subject in the curriculum to help students develop holistically in the physical, emotional, spiritual and the intellectual domains.…”
Section: Introductionmentioning
confidence: 99%